Magnetic Resonance Imaging Findings in 13 Neurologic Pot-Bellied Pigs - Castel, Aude; Doré, Vincent; Vigeral, Mariana; Hecht, Silke (Frontiers in Veterinary Science, 2020)
This study reports the magnetic resonance imaging (MRI) findings in thirteen pot-bellied pigs presented to our institution with neurological deficits. Nine pigs had abnormal MRI findings (7 with spinal cord localization and 2 with brain localization), with three of them having histopathological confirmation of the diagnoses. MRI diagnoses included a myopathy suspected to be secondary to Erysipelothrix rhusiopathiae, a round cell neoplasia involving the vertebral canal, myelomalacia, a cervical cyst like like extradural lesion, pelvic fracture with secondary cauda equina involvement, two cases of fibrocartilaginous embolism or acute non-compressive nucleus pulposus extrusion, multifocal brain infarcts, and a cystic fourth ventricle dilation resulting in obstructive hydrocephalus and syringomyelia. Four pigs had normal MRI studies, with one of them ultimately diagnosed with idiopathic vestibular disease. This retrospective study illustrates the wide variety of diagnoses achieved with MRI of the head or vertebral column in pigs, several of them having never been described in this species. Some of the conditions identified had a good outcome. This justifies using MRI as an ante-mortem diagnostic tool as it can provide relevant information about the prognosis which can significantly influence treatment recommendations. Our findings suggest that MRIshould be considered as a valuable imaging modality, when feasible, in pigs with neurological deficits.